Digital Marketing and Consumer Experience in Building Brand Green Innovation in SMEs: The Trend Analysis Using a Bibliometric Analysis - Anugerah Dachi; Susilo Utomo; Elly Siti Nurliyah; Teguh Prakoso; Rina Apriliani (Universitas KH. Abdul Chalim Mojokerto, 2025)
SMEs play a key role in promoting environmental sustainability. One important aspect is the adoption of green innovation to enhance environmental performance. This study explores research trends on green innovation in SMEs using bibliometric analysis based on 229 publications from the Web of Science database. The analysis, conducted with VOSviewer, covers publication patterns, leading journals, most cited and productive authors, keyword trends, and future research directions. The Journal of Cleaner Production emerged as the top journal, while Afum Ebenezer, Agyabeng-Mensah, and Charles Dad were among the most prolific authors. Jiangsu University was the most productive institution. Future research is expected to explore themes like open innovation, green HRM, green finance, and competitive advantage. This study is limited to SMEs and the Web of Science database, suggesting the need for broader future studies across other sectors. This bibliometric analysis contributes new insights into the intersection of green innovation and SMEs.